The Comparison of Soundness Level of Islamic Banks in Indonesia and Malaysia - Muhamad Nadratuzaman Hosen; Syafaat Muhari (ETIKONOMI, 2018)
This study was conducted to analyze the soundness comparison of Islamic banks in Indonesia and Malaysia to measure the readiness of Islamic banks in both countries In facing of financial integration in the ASEAN Economic Community (AEC) by 2020. The study uses data of annual financial statements in 10 Islamic banks in each country in period 2012-2014 using CAMEL Method. The results of this study indicate that Islamic banks in Malaysia are relatively better prepared compared to Islamic banks in Indonesia. Islamic Banks in Malaysia tend to be more soundness than Islamic Banks in Indonesia during periods of 2012 to 2014.  The implication based on finding indicated that the Islamic banks in Indonesia need improvement in the product diversification both on financing or funding to compete in ASEAN Region.DOI: 10.15408/etk.v17i1.6711